Repertório barroco e suas possibilidades ao violão: aspectos teóricos e métodos transcritivos a partir das cordas dedilhadas - Cardoso, Renato de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study proposes a dialogue across fields of Early Music and the Interpretative Practices in modern instruments. For this, it discusses the ideological basis of the Historically Informed PerformanceMovement which tends to create a distance between such areas, especially the paradigmatic association between early music and period instruments. Aiming to develop a method of arrangement of the repertoire of baroque guitar, theorbo and baroque lute for the modern guitar, this study has departed from the literature review of editions and academic literature about guitar arrangement of the baroque repertoire, with emphasis on the aforementioned instruments. These publications have been classified according to their method of transcription, thus categorizing them from the alteration of the tuning of the guitar. I propose the direct arrangement method to the repertoire of plucked string instruments of the Baroque, which consists of changing the guitar tuning according to the reference instrument's repertoire, allowing a direct reading of the tablature, with delimited tools for adaptation of the musical text, without the need of editing the music. Thisproposal allows for a perennial contact with the primary sources and its notation forms, in addition to providing an ease of execution and a large amount of arrangement.

Este trabalho propõe um diálogo entre as áreas de Música Antiga e de Práticas Interpretativas em instrumentos modernos. Para tal empreitada, discute as bases ideológicas do Movimento de PerformanceHistórica que tendem a um distanciamento entre as áreas, especialmente a associação paradigmática entre Música Antiga e instrumentos de época. Com a finalidade de elaboração de um método transcritivo para o violão do repertório de guitarra barroca, alaúde barroco e teorba,partiu-se da revisão bibliográfica de edições e textos acadêmicos que tratam da transcrição do repertório barroco ao violão, com ênfase nestes instrumentos. Essas publicações foram classificadas de acordo com seu método de transcrição, categorizando-as a partir da alteração da afinação do violão. Para o repertório dos instrumentos de cordas dedilhadas do Barroco, proponho como método a transcrição direta, que consiste na mudança da afinação do violão de acordo com o instrumento referencial do repertório, permitindo uma leitura direta da tablatura, com ferramentas delimitadas para adaptação do texto musical, sem a necessidade de confecção de uma edição musical.Essa proposta permite um contato perene com as fontes primárias e seus modos de escrita, além de propiciar uma facilidade de execução e um volume elevado de transcrições.
Keywords: Violão; Performance (Arte); Música - Séc. XVIII; Guitar